The Antibacterial Activity of Chitosan Products Blended with Monoterpenes and Their Biofilms against Plant Pathogenic Bacteria. (4th April 2016) - Badawy, Mohamed E. I.; Rabea, Entsar I.; Taktak, Nehad E. M.; El-Nouby, Mahmoud A. M.
Abstract : This study focuses on the biological activities of eleven chitosan products with a viscosity-average molecular weight ranging from 22 to 846 kDa in combination with the most active monoterpenes (geraniol and thymol), out of 10 tested, against four plant pathogenic bacteria, Agrobacterium tumefaciens, Erwinia carotovora, Corynebacterium fascians, and Pseudomonas solanacearum . The antibacterial activity was evaluated in vitro by the agar dilution technique as a minimum inhibitory concentration (MIC) that was found to be dependent on the type of the microorganism tested. The most active product of chitosan was used for biofilm production enriched with geraniol and thymol (0.1 and 0.5%) and the films were also evaluated against the tested bacteria. The biological bioactivities summarized here may provide novel insights into the functions of chitosan and some monoterpenes and potentially allow their use for food protection from microbial attack.